The impact of an intervention programme on the decision making speed and accuracy, declarative knowledge, and selected visual skills of u/20 rugby players - Uys, S. (University Stellenbosch, 2008)
The purpose of this study was to determine the effectiveness of a 16-week multidimensional intervention programme on the speed and accuracy of decision making, declarative knowledge and visual skills of u/20 rugby players. Two intact groups of rugby academy players participated in this study. One academy group participated in the intervention programme, which included activities, including the statistical analysis of individual players, game analysis, tactical rugby discussions, rugby rule discussions and visual skills training. The other academy group served as the comparison group and completed both the pre- and post-tests. The results indicated significant improvements in the speed of tactical decision making by participants in both the experimental and the comparison groups. Both groups also indicated a significant deterioration in the accuracy of their decisions. Both groups achieved a significant improvement in their declarative knowledge of rugby rules, as well as in their visual skills. The similarity in the post-test scores of the two groups led to the conclusion that the intervention programme, as presented in this study, did not appear to make a significant impact on the players. Suggestions are made for the design of future intervention programmes to improve tactical decision making.